Foreign Bank Supervision and Challenges to Emerging Market Supervisors - Song, In (IMF Working Papers; Working Paper ;, 2004)
The increased presence of foreign banks in a country's domestic banking system necessitates the development of effective cross-border prudential supervision where the consolidated supervision is the essential element. This paper presents foreign bank supervision in terms of division of responsibilities between the home and host countries, consolidated supervision, quality of home-country supervision, memoranda of understanding (MOUs), and "ringfencing" of banks. A number of challenges which foreign banks bring to emerging market banking supervisors are also discussed. The paper also provides surveys of country cases.